The Environmental Factors Associated With Fatigue of Frontline Nurses in the Infection Disease Nursing Unit - Ma, Ming; Adeney, Michael; Long, Hao; He, Baojie (Frontiers in Public Health, 2021)
The workload in the Infection Disease Nursing Unit (IDNU) is increasing dramatically due to COVID-19, and leads to the prevalence of fatigue among frontline nurses, threatening their health and safety. The built environment could fundamentally affect nurses’ fatigue for a long-term perspective. This article aims to extract the environmental (design) factors of IDNU and explore nurses’ perceptions of these factors on the fatigue, in order to produce resources to mitigate the fatigue by environmental interferons. A cross-sectional design is employed by a mixed method of focus group interview and written survey. Environmental factors are collected from the focus group interview of healthcare design experts (n=8). Nurses (n=64) with frontline experiences in IDNU are recruited to assess these factors in the survey. Four categories of environmental factors are extracted: nursing distance, spatial crowdness, natural light and ventilation, spatial privacy. Among them, nursing distance is considered as the most influential factor on physical fatigue, while spatial privacy is that on psychological fatigue. Generally, these environmental factors are found to be more influential on physical fatigue than psychological fatigue. The hierarchy of technical titles could affect nurses’ perceptions of these factors on the fatigue to various extent. Low-ranking nurses (nurse assistant, practical nurse) are more likely to suffer from physical fatigue than high-ranking nurses (senior nurse), who are mainly affected on the psychological fatigue. The result shows that environmental design could affect nurses’ fatigue, particularly on the physical aspect. Environmental interventions such as reducing the nursing distance and improving the spatial privacy could alleviate nurses’ fatigue. Targeted environmental measures should be adopted to fit nurses’ specific conditions Since, as they may receive diverse impacts of these factors due to their roles. More attention should be given low-ranking nurses, who accounts for the majority and more vulnerable to the physical fatigue.